Potential of Small-wind Turbine for Power Generation on Offshore Oil and Gas Platforms in Malaysia - Yan, Chee Sze; Lim, Siow Chun; Yoong, Chan Kah (International Journal of Energy Economics and Policy, 2022)
On most of the offshore oil and gas platforms, the current means of generating power are through the use of generators i.e. gas turbines and diesel power generators, or micro-generators for some smaller equipment. These generator sets are less reliable, especially on unmanned platforms. Hence, the deployment of renewable energy, such as the use of wind turbines, would be better for energy security, economic development and also protection of the environment. Instead of using wind power to power up the whole platform, small wind turbines can be utilised to power up some utilities and instrumentations on the platform, while having generators as back up, as the wind speed is beyond control. However, the capability of a small wind turbine in generating enough power is constantly under doubt as it is yet to be widely employed and only meagre data is available. This is caused by the issue of having insufficient studies regarding the implementation of small wind turbines for power generation on offshore oil and gas platforms. Hence, this paper studied the capability of small wind turbines for power generation on offshore platforms in Malaysia. Several models of small wind turbines were selected and their abilities in generating power to fulfil the annual energy consumption on a typical offshore platform were examined through precise calculations. The common offshore locations in Malaysia were identified and the average wind speeds from 2017 to 2019 at these locations were analysed. The result shows that certain models of small wind turbines are able to provide a significant amount of power for an offshore platform especially to power up the low power machineries. It was found that Kerteh, Terengganu is the most suitable offshore location to harness wind power due to its averagely high wind speed throughout the year. The highest amount of energy that can be produced was around 1445kWh per annum at Kerteh by the small wind turbine with the largest swept area and the lowest cut-in speed. This paper aims to serve as numerical validation on the plausibility of integrating small wind turbines for the generation of electricity on offshore platforms in Malaysia while also providing the recommended locations that are suitable for this region.